2017
DOI: 10.1093/neuros/nyw136
|View full text |Cite
|
Sign up to set email alerts
|

Far-Lateral Approach Without Drilling the Occipital Condyle for Vertebral Artery–Posterior Inferior Cerebellar Artery Aneurysms

Abstract: A far-lateral approach that leaves the occipital condyle intact is adequate for treating most patients with VA-PICA aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…For many years, controversy has raged over the pros and cons of the various surgical routes to approach PICA aneurysms. The far-lateral approach is a standard approach for PICA aneurysms clipping 75 , 77 , 78 , 82 , 83 .…”
Section: Aneurysmmentioning
confidence: 99%
“…For many years, controversy has raged over the pros and cons of the various surgical routes to approach PICA aneurysms. The far-lateral approach is a standard approach for PICA aneurysms clipping 75 , 77 , 78 , 82 , 83 .…”
Section: Aneurysmmentioning
confidence: 99%
“…We agree with those authors who believe that the resection of condyles is unnecessary in the vast majority of cases. [24,28] In some cases, the optimal surgical view may be achieved through intradural jugular tuberclectomy. [2,17,27]…”
Section: Discussionmentioning
confidence: 99%
“…18 Another recent report of a modified far-lateral approach without condyle resection in 56 patients with VA and PICA aneurysms reported that this less-invasive approach also offers excellent surgical exposure, with complete occlusion rate achieved in all patients and good clinical outcome (Glasgow Outcome Scale score 4e5) achieved in 52 patients (93%). 43 Our series comprises 52 consecutive cases with a comparable favorable outcome of 100% in unruptured and 71% in good-grade patients.…”
Section: Discussionmentioning
confidence: 99%